Mortgage Durée: Towards a Politics 'In Construction'. Issue 3 (27th May 2017) - Corsín Jiménez, Alberto
ABSTRACT: The article offers an ethnographic analysis of the imagination of the city as a mortgage environment: a space of sociability mediated by interest rates, legal language, square metres, actuary calculations and temporalities, real estate brokers, political and financial corruption, and so on. A central aim is to understand what it may mean for our contemporary political theory and anthropology to say that a society's democratic imagination rests on a real estate and mortgage ontology. Such an imagination renders the city as a political project 'in construction': an ongoing, 'building-in-progress' development, whose social rhythm is inflected by a permanent temporal and spatial suspension; a holding in abeyance characterised by the hopeful and yet fearful economy of credit. The mortgage durée of a city-in-construction delineates the contours of our political ruins, but in this ruinous circumstance, amidst the hubris, it offers also the resources and materials for critique and reconstruction.